Análisis fenomenológico del juego infantil como modalidad de la fantasía perceptiva - Luna Bravo, José Luis (2023)
The experience of playing is not unknown to anyone of us. As children we have all entered the world opened by phantasy and toys. This paper makes explicit —from a phenomenological perspective— how this particular mixture of perception and phantasy takes place. To avoid confusing this experience with a hallucination or a mere simulation, I claim that playing can be analysed as a particular modality of perceptual phantasy in the “as if” mode. This modality,based on the neutralisation of a perceptual apprehension, enables the opening of the world of phantasy that is deployed in playing. Accordingly, this paper isdivided in 3 parts: First, I present a general description of phantasy consciousness; then, I propose an analysis of perceptual phantasy in the experience of theatre; third, I describe the specificity of this modality of phantasy consciousness —called perceptual phantasy— in the intentional structure proper of children’s playing.